WRITTEN ENGLISH AT PUBLIC SPACES IN PADANG : A COMMUNICATION TOOL OR A BRANDING LANGUAGE? - Oktavianus Oktavianus; Yusmalinda Yusmalinda; Dian Purnama Sari; Ferdinal Ferdinal; Mita Handayani (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2026)
This study examined whether written English serves as a communication tool or a branding language in Padang. The study focuses on English as a communication tool and branding language, its structural features as a branding language, and the motives for using it in this capacity. This study uses a qualitative, quantitative, and Linguistic Landscape approach. The Data for this study are the use and placement of English in public spaces in Padang City, including on public roads, markets, malls, hotels, cafes, the names of business units, tourist attractions, and other strategic places. The questionnaire was distributed via Google Forms to 94 respondents to gather their views on the role of English as a branding language. Written English posted or used in public spaces, as mentioned above, was photographed. Data analysis was conducted using the intralingual extralingual method. The results of this study indicate that written English in public spaces in Padang primarily serves as branding language. When compared with Indonesian and Minangkabau, English and Minangkabau are more likely to convey information. Except for places like hotels and educational institutions, especially universities, English serves as both a branding language and a means of conveying information.